Primary Failure Eruption: Genetic Investigation, Diagnosis and Treatment: A Systematic Review - Francesco Inchingolo; Irene Ferrara; Fabio Viapiano; Anna Maria Ciocia; Irene Palumbo; Mariafrancesca Guglielmo; Alessio Danilo Inchingolo; Andrea Palermo; Ioana Roxana Bordea; Angelo Michele Inchingolo; Daniela Di Venere; Gianna Dipalma (MDPI AG, 2023)
Aim: The aim of this systematic review is to explore the pathology, diagnosis, treatment, and genetic basis of Primary Failure of Eruption (PFE) in the field of pediatric dentistry and orthodontics. Methods: The Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines were followed for this review. The databases PubMed, Science Direct, Scopus, and Web of Science were searched from 1 July 2013 to 1 July 2023, using keywords "primary failure of tooth eruption" OR "primary failure of eruption" OR "tooth eruption failure" OR "PFE" AND "orthodontics". The study selection process involved screening articles based on the inclusion and exclusion criteria. Results: A total of 1151 results were obtained from the database search, with 14 papers meeting the inclusion criteria. The review covers various aspects of PFE, including its clinical features, diagnosis, treatment options, and genetic associations with mutations in the PTH1R gene. Differentiation between PFE and Mechanical Failure of Eruption (MFE) is crucial for accurate treatment planning. Orthodontic and surgical interventions, along with multidisciplinary approaches, have been employed to manage PFE cases. Genetic testing for PTH1R mutations plays a significant role in confirming the diagnosis and guiding treatment decisions, although some cases may not be linked to this mutation. Conclusions: This systematic review provides valuable insights into the diagnosis, treatment, and genetic basis of PFE. Early diagnosis and personalized treatment planning are crucial for successful management. Genetic testing for PTH1R mutations aids in accurate diagnosis and may influence treatment decisions. However, further research is needed to explore the complex genetic basis of PFE fully and improve treatment outcomes for affected individuals.